2014
DOI: 10.1002/wps.20090
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic application of the experience sampling method in the treatment of depression: a randomized controlled trial

Abstract: In depression, the ability to experience daily life positive affect predicts recovery and reduces relapse rates. Interventions based on the experience sampling method (ESM-I) are ideally suited to provide insight in personal, contextualized patterns of positive affect. The aim of this study was to examine whether add-on ESM-derived feedback on personalized patterns of positive affect is feasible and useful to patients, and results in a reduction of depressive symptomatology. Depressed outpatients (n5102) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
282
2
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 249 publications
(303 citation statements)
references
References 48 publications
(73 reference statements)
7
282
2
12
Order By: Relevance
“…This theory is in agreement with the current finding that it is not the presence and the central place in the network of depressive mood, but rather the absence or non-central role of positive affect that marks the difference between the depressive and hypomanic period. Insight in ESM-based mood networks may aid treatment, as previous research showed that ESM-derived feedback on positive affect results in a lasting decrease in depressive symptomatology [20].…”
Section: Comparison Of Results With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This theory is in agreement with the current finding that it is not the presence and the central place in the network of depressive mood, but rather the absence or non-central role of positive affect that marks the difference between the depressive and hypomanic period. Insight in ESM-based mood networks may aid treatment, as previous research showed that ESM-derived feedback on positive affect results in a lasting decrease in depressive symptomatology [20].…”
Section: Comparison Of Results With Literaturementioning
confidence: 99%
“…Feedback using individual ESM data focussing on positive affect has been associated with decreases in depressive symptoms [20] and, thus, may serve to neutralise negative affective states. Based on the present results and results from a previous n=1 study [8], we may conclude that the prolonged use of ESM can help in treatment.…”
Section: Implications and Treatmentmentioning
confidence: 99%
“…Accordingly, Kramer et al provided feedback to momentary positive affect reported by depressed patients, which led to an improvement of depressive symptoms [27]. An emotion-aware mobile system has the potential to bypass the requirement of subjective reporting and directly provide intervention.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Traditionally, ESM studies have been conducted using an external signalling device (such as a pager or pre-programmed electronic watch) coupled with paperbased forms for participants to fill out when the device emits a signal [2]. This cumbersome and unreliable approach has been greatly improved upon in recent years, where researchers have recognised the potential of mobile applications for conducting these types of studies with participants [3], [4], [5]. Along with this, in the field of Human Computer Interaction (HCI) study applications have been developed which allow both the signalling and data collection to take place on a participant's personal device.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers behind EmotionSense have provided open-source libraries for facilitating the creation of ESM applications, but utilising these libraries still requires Android programming experience. Instead, non-programmers must invest in commercial software or hardware [3], [4], [5], hire professional developers [8], employ manual methods such as telephoning participants [9] or simply resort to providing paper-based logs [2], [10].…”
Section: Introductionmentioning
confidence: 99%